Wireless kayak on-water ergometry - Part 1: Paddle blade force - Sturm, D.; Yousaf, K.; Brodin, L.-A.; Halvorsen, K. (Sports Technology, 2013)
The aim of this work was to present a new wireless paddle force measurement system and to evaluate this measurement system. The system is redeveloped from a previous design and includes inertial motion sensors, which allows for the movement and inertia of the paddle to be taken into account. The system consists of two sensor nodes, designed for quick attachment to virtually any kayak paddle and an Android phone or tablet. Each sensor node measures the bending of the shaft in one plane. We derive the expressions necessary for computing the force on the paddle blade in two directions, ignoring the force in the direction of the shaft. Two different schemes for calibrating the system are presented. The accuracy and reliability of the system is evaluated in a laboratory setting using a material testing machine. An average error of 0.4% can be achieved for force measurements following directly after calibration. When the sensors are removed and reattached between calibration and measurements, average error between loading and measured force increased to 2.0% (linear model) and 1.8% (quadratic model). The limits of agreement depend on the position of the sensor nodes along the shaft and the feather angle if transverse sensitivity of the sensors is used to determine two-dimensional force on the paddle blade. On-water stroke force is presented, averaged over 10 strokes for each side with force levels >200 N to show the applicability of the study. The accuracy of the measurement is affected by the calibration method, placement of the paddle nodes and the shaft's properties.